Subventricular Zone‐Derived Oligodendrogenesis in Injured Neonatal White Matter in Mice Enhanced by a Nonerythropoietic Erythropoietin Derivative123. (20th September 2012) - Kako, Eisuke; Kaneko, Naoko; Aoyama, Mineyoshi; Hida, Hideki; Takebayashi, Hirohide; Ikenaka, Kazuhiro; Asai, Kiyofumi; Togari, Hajime; Sobue, Kazuya; Sawamoto, Kazunobu
Abstract: Perinatal hypoxia‐ischemia (HI) frequently causes white‐matter injury, leading to severe neurological deficits and mortality, and only limited therapeutic options exist. The white matter of animal models and human patients with HI‐induced brain injury contains increased numbers of oligodendrocyte progenitor cells (OPCs). However, the origin and fates of these OPCs and their potential to repair injured white matter remain unclear. Here, using cell‐type‐ and region‐specific genetic labeling methods in a mouse HI model, we characterized the Olig2‐expressing OPCs. We found that after HI, Olig2+ cells increased in the posterior part of the subventricular zone (pSVZ) and migrated into the injured white matter. However, their oligodendrocytic differentiation efficiency was severely compromised compared with the OPCs in normal tissue, indicating the need for an intervention to promote their differentiation. Erythropoietin (EPO) treatment is a promising candidate, but it has detrimental effects that preclude its clinical use for brain injury. We found that long‐term postinjury treatment with a nonerythropoietic derivative of EPO, asialo‐erythropoietin, promoted the maturation of pSVZ‐derived OPCs and the recovery of neurological function, without affecting hematopoiesis. These results demonstrate the limitation and potential of endogenous OPCs in the pSVZ as a therapeutic target for treating neonatal white‐matter injury. STEM Cells 2012;30:2234–2247